2013
DOI: 10.1371/journal.pone.0060321
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics and Genetic Heterogeneity between Carcinoma-Associated Fibroblasts and Their Paired Normal Fibroblasts in Human Breast Cancer

Abstract: BackgroundThe extensional signals in cross-talk between stromal cells and tumor cells generated from extracellular matrix molecules, soluble factor, and cell-cell adhesion complexes cooperate at the extra- and intracellular level in the tumor microenvironment. CAFs are the primary type of stromal cells in the tumor microenvironment and play a pivotal role in tumorigenesis and development. Hitherto, there is hardly any systematic analysis of the intrinsic relationship between CAFs function and its abnormal sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 47 publications
7
80
0
Order By: Relevance
“…Previous studies have shown that CCL-18 also has the ability affect tumorigenesis, and can affect the grade and prognosis of ovarian, colon, and gastric cancers. In the treatment of breast cancer with carcinoma-associated fibroblast (CAF) regimen, Peng et al (2013) found that breast cancer cells co-cultured with CAF resulted in increased CCL-18 secretion, which promoted the invasion and metastasis of breast cancer cells. Furthermore, Nariţa et al (2011) found that breast cancer patients with elevated serum CCL-18 levels were associated with poor disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CCL-18 also has the ability affect tumorigenesis, and can affect the grade and prognosis of ovarian, colon, and gastric cancers. In the treatment of breast cancer with carcinoma-associated fibroblast (CAF) regimen, Peng et al (2013) found that breast cancer cells co-cultured with CAF resulted in increased CCL-18 secretion, which promoted the invasion and metastasis of breast cancer cells. Furthermore, Nariţa et al (2011) found that breast cancer patients with elevated serum CCL-18 levels were associated with poor disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs and normal fibroblasts (NFs) were isolated from breast tumor tissues and their normal counterparts as described previously [1,11]. The normal counterparts were defined in the noncancerous region of breast tissue at least 2 cm away from the outer tumor margin.…”
Section: Isolation Of Primary Fibroblasts and Culture Of Cellsmentioning
confidence: 99%
“…Based on data collected by the World Health Organization (WHO), 1.4 million women suffered from breast cancer in 2006, and 0.4 million patients died of the cancer (Smigal et al, 2006). In China, the mortality and morbidity of breast cancer has increased annually, and there is now 1 death every 12 min (Peng et al, 2013) and more than 40 in 100,000 women are diagnosed with breast cancer per year in some cities (Leidenius et al, 2003;Zhao et al, 2013). Even worse, the morbidity of breast cancer has been increasing rapidly, by about 3 to 4% every year (Yan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%